Sylvia and Marsha start a revolution! : the story of the trans women of color who made LGBTQ+ history - Ellison, Joy Michael; Silver, Teshika (London : Jessica Kingsley Publishers, 2021)
Introduces children to the story of Sylvia Rivera and Marsha P. Johnson, the two transgender women of color who helped kickstart the Stonewall Riots and dedicated their lives to fighting for LGBTQ+ equality. It introduces children to issues surrounding gender identity and diversity, accompanied by a reading guide and teaching materials to further the conversation.
School Library Journal, January 2021
2.3.
K-3.
Some copies donated by GLSEN as part of the Rainbow Library November 2021.
Keywords: Rivera, Sylvia, -- 1951-2002 -- Juvenile literature; Johnson, Marsha P., -- 1944-1992 -- Juvenile literature; Minority transgender women -- United States -- Biography -- Juvenile literature; Rivera, Sylvia, -- 1951-2002.; Johnson, Marsha P., -- 1944-1992.; Minority transgender women; LGBTQ+ nonfiction picture book; Biographies; Transgender